2021
DOI: 10.1108/ijm-03-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

A cross-level examination of team-directed empowering leadership and subordinates' innovative performance: an AMO theory perspective

Abstract: PurposeIn the field of innovation, individual innovative performance also has an important impact on team and organizational innovative performance, thus it is necessary to identify factors that increase individual innovative performance. One key to unlock individual innovative performance is empowering leadership. Drawing on the Ability-Motivation-Opportunity (AMO) theoretical framework, this study investigates the cross-level influence of team-directed empowering leadership on subordinates' innovative perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Consequently, employee improvisation can be stimulated. Previous research has found that empowering leadership positively predicts employee innovation behavior, 29 taking charge, 31 and voice. 32 Based on the theoretical background and empirical research mentioned above, we propose the following hypothesis:…”
Section: Empowering Leadership and Employee Improvisationmentioning
confidence: 93%
See 2 more Smart Citations
“…Consequently, employee improvisation can be stimulated. Previous research has found that empowering leadership positively predicts employee innovation behavior, 29 taking charge, 31 and voice. 32 Based on the theoretical background and empirical research mentioned above, we propose the following hypothesis:…”
Section: Empowering Leadership and Employee Improvisationmentioning
confidence: 93%
“…Therefore, employees are more willing to engage in tasks that lie outside their defined work roles, such as actively identifying new work procedures. 29 Second, by conveying information related to work meaning, communicating work progress and sharing resources with employees, empowering leaders can easily allow employees to realize their importance to the organization and enhance their sense of responsibility. 30 Empowering leadership also encourages employees to participate in decision-making to enhance their sense of self-worth.…”
Section: Empowering Leadership and Employee Improvisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, humble leaders appreciate the strengths and contributions of their subordinates, acknowledge their work abilities, encourage role exchange between leaders and subordinates and give subordinates more opportunities for trial and error (Owens and Hekman, 2012), which will help motivate their subordinates (Ma et al ., 2020). According to AMO (ability, motivation and opportunity) theory, individual work behavior is influenced by a combination of three factors: competence, motivation and opportunity (Cui and Yu, 2021). Studies have shown that both internal motivation and work competence are negatively related to procrastination (Codina et al ., 2018).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Combining Hypothesis 1 with Hypotheses 2 and 3, we anticipated that employee strengths use serves as a mediator in the relationship of strengths-based HR system with task performance and with innovative behavior. According to AMO model, employees who have the ability, motivation, and opportunity to execute a given behavior are more apt to perform the behavior, such behavior will further impact employees’ job performance (Cui & Yu, 2021). Based on this logic and Hypotheses 1–3, it is reasonable to expect that strengths-based HR system positively influences employee strengths use and, in turn, task performance and innovative behavior of employee.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%